Substance Involvement and Probation Outcomes: Evidence From a Cohort Study - Galvin, Miranda A. (Journal of drug issues, 2022)
Substance use disorders are common among justice-involved populations, the majority of whom are under community supervision in the form of probation. Substance involvement can amplify the challenges of complying with requirements of probation supervision, violations of which can lead to incarceration. In this study, we assess the role of substance involvement in violations of probation conditions across 47 counties representing 70% of individuals sentenced to probation in the state of Pennsylvania. We also consider the role of court-ordered treatment. We conclude by estimating the consequences of resentencing for substance-involved individuals in Pennsylvania (in incarceration and supervision days). Results suggest that individuals who are substance-involved are at greater risk of technical violations. However, treatment may reduce some negative outcomes for substance-involved individuals. Court-ordered treatment was associated with a reduction in the likelihood of being resentenced for a new offense relative to individuals who were substance-involved but not ordered to treatment.